Frank Capra's Why we fight [videorecording (DVD)]. - Capra, Frank, 1897-1991 (Timeless Media Group, 2005)
In Dec. 1941 America was forced into World War II by the Japanese attack on Pearl Harbor. The US government sponsored this series of films created by director Frank Capra to explain its official war policy. Narrated with classical music.